KEPEMIMPINAN DALAM PERSPEKTIF TRI HITA KARANA - Nuraeni, Nuraeni (Universitas Pendidikan Mandalika, 2023)
AbstractThis study aims to describe Describing Leadership in the Tri Hita Karana Perspective. The method used in literature studies is library research. The results of the study are: 1) THK Views the existence of leaders as protectors for their followers. 2) Leaders who are able to control themselves from the temptation of the five senses by prioritizing reason. 3) Leaders who serve with good intentions on the basis of God. 4) The leader sets an example to his subordinates. 5) Leaders have guidelines (religion, formal law, ethics, etiquette and customary law). 6) Leaders who have spiritual character. 7) The leader who has eight temperaments: Sun temperament, Moon temperament, Star disposition, Wind disposition, Cloud disposition, Fire disposition, Ocean disposition, and Earth disposition. 8) leaders who prioritize deliberation and consensus.Keywords: Leadership, Tri Hita Karana